2018
DOI: 10.1111/wej.12391
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of different membrane types in the textile mercerization wastewater treatment

Abstract: This study investigates the performance of three ultrafiltration membranes, i.e. a submerged polyethylene (PE) hollow fibre membrane, a multibore polyethersulfone (PES) membrane and a tubular multichannel ceramic membrane in the textile mercerization wastewater treatment. Experiments were carried out on two laboratory dead end membranes and on a cross flow membrane set‐up using wastewater with and without the addition of MgCl2 as a coagulant. Investigation into energy consumption was also carried out. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Some researchers reported that causticization processes discharges were having high NaOH concentrations (60-70 g/L), highly colored (4000-10000 Pt-Co) and various organic and inorganic pollutants (Lu et al, 2009) (Varol, 2008) (Varol et al, 2015). The most recent research reported that mercerization wastewaters were heavily organic loaded and were having significant amounts of NaOH, surfactants and suspended solids (Ağtaş et al, 2021b;Zebić Avdičević et al, 2019.…”
Section: Wastewater Characterization Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers reported that causticization processes discharges were having high NaOH concentrations (60-70 g/L), highly colored (4000-10000 Pt-Co) and various organic and inorganic pollutants (Lu et al, 2009) (Varol, 2008) (Varol et al, 2015). The most recent research reported that mercerization wastewaters were heavily organic loaded and were having significant amounts of NaOH, surfactants and suspended solids (Ağtaş et al, 2021b;Zebić Avdičević et al, 2019.…”
Section: Wastewater Characterization Resultsmentioning
confidence: 99%
“…If the suspended solids content is removed by the UF process, alkali solution and surfactants can be reused in the process (Zebić Avdičević et al, 2017). In the literature, there are limited studies on the treatment of highly alkaline textile wastewater and the recovery of caustic soda (Ağtaş et al, 2021a;Choe et al, 2005;Zebić Avdičević et al, 2017, 2019. Choe et al, 2005 investigated the effectiveness of the NF process for caustic recovery from alkaline wastewaters from the processing of polyester fabrics in the textile industry.…”
Section: Introductionmentioning
confidence: 99%
“…The operation of ultra-filtration membrane can be achieved in two different service modes, which are dead-end flow and cross-flow [49][50][51]. The dead-end flow mode of ultra-filtration membrane operation is similar to a cartridge filter wherein there is only a filtrate flow and feed flow.…”
Section: Ultra-filtration Membrane Technologymentioning
confidence: 99%
“…During mercerization, the cellulose molecule is mainly transformed into soda cellulose, which promotes dyeing and adhesive rates in light to dark colours [41]. For this procedure to be sustainable, the concentration of sodium hydroxide must be reduced to get the mercerized effect [42][43][44].…”
Section: Mercerizationmentioning
confidence: 99%